Penerapan Cooperative Learning Pada Pembelajaran Daring Mata Pelajaran Informatika Ditinjau Dari Keaktifan dan Prestasi Belajar Siswa di SMP. - Rifa'i Abdul Karim; Dwi Maryono; Febri Liantoni (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
This study aims to increase student activity and learning achievement through the application of Cooperative Learning Type STAD in Informatics online learning by utilizing the Google Jamboard application. This research is included in the quasi-experimental type of research with the design of One Group Pretest-Posttest. The population in this study was all grade VII students of a state owned school. The sample used was class VII G students with a total of 32 students. The sampling technique uses cluster random sampling. Data collection techniques use questionnaires and tests. The technologyk data analysis used is a normality test, homogeneity test, and hypothesis test using a paired sample t test. The results of the study, which were reviewed in terms of learning activity, statistically there was an increase from an average score of 72.90 to 80.69. Meanwhile, in terms of learning achievement, it showsthat statistically the average pre-test score is46.56 and the average post test score is 65.03 so that there is an increase through the application of Cooperative Learning Type STAD in informatics online learning.